Patterns of injuries to children on public playgrounds. Issue 4 (October 1994) - Mott, A; Evans, R; Rolfe, K; Potter, D; Kemp, K W; Sibert, J R
Abstract : The incidence and pattern of injuries to children in public playgrounds presenting to the accident and emergency department were reviewed over two six month summer periods in Cardiff. A total of 178 children (mean age 7.5 years) attended with a playground injury representing 1.1% of all the children attending. One hundred and five children fell from equipment, of which the commonest was the climbing frame; 125 children had playground surface related injuries, 86 on bark and 30 on concrete. The pattern of injuries on the playground surfaces was different: fractures and sprains were more common on bark surfaces and lacerations and abrasions on concrete surfaces. Comparison of total injury rates showed there were fewer injuries on modernised playgrounds than expected but these differences were not significant. Modernised playgrounds are more popular, have new exciting equipment, and offer good play opportunities for children. However, the high fracture rate on modernised bark playgrounds is concerning and requires further research.